Blockchain as a service models in the Internet of Things management: Systematic review. Issue 4 (18th October 2020) - Li, Daming; Deng, Lianbing; Cai, Zhiming; Souri, Alireza
Abstract: Today, blockchain uses a list of various blocks for storing a distributed flat of invariable information that informs of a set of replicated logical things in the Internet of Things (IoT). In the blockchain, a set of blocks includes various transactions containing a cryptographic hash value and a timestamp. Blockchain‐as‐a‐service (BaaS) as a new service in cloud providers presents an infrastructure for accessing users to execute, manage, and monitor blockchain applications without high secured infrastructure requirements. Recently, BaaS concepts widely have used the management of IoT applications in different layers such as network, data, control, and resource. This paper provides a systematic review of recent research studies in BaaS models. The main goal behind this review is to categorize the applied scenarios, trends, evaluated Quality of Service (QoS) factors, new challenges, and open directions on BaaS models in IoT management. To evaluate the existing research studies in this field, five analytical research questions are proposed to analyze the technical aspects of each study. The analytical results based on existing research questions specify that the BaaS models are applied to network layer to manage IoT environment more than other layers. Also, security and privacy are two important factors to evaluate the existing BaaS models in cloud‐edge IoT environments. Finally, the integration of BaaS models on IoT environments with interconnections of cloud‐edge computing and software defined networks creates great secure opportunities for smart environment applications to monitor, manage, and improve all the atomic services and resources. Abstract : This paper provides a systematic review of recent research studies in BaaS models. The main goal behind this review is to categorize the applied scenarios, trends, evaluated Quality of Service (QoS) factors, new challenges, and open directions on BaaS models in IoT management. To evaluate the existing research studies in this field, five analytical research questions are proposed to analyze the technical aspects of each study. The analytical results based on existing research questions specify that the BaaS models are applied to network layer to manage IoT environment more than other layers. Also, security and privacy are two important factors to evaluate the existing BaaS models in cloud‐edge IoT environments. Finally, the integration of BaaS models on IoT environments with interconnections of cloud‐edge computing and software defined networks creates great secure opportunities for smart environment applications to monitor, manage, and improve all the atomic services and resources.